Nerve Growth Factor and its Receptor TrkA Serve as Potential Markers for Human Corneal Epithelial Progenitor Cells - Qi, Hong (2007)
Nerve growth factor (NGF), a member of the neurotrophin family, has been identified as an essential growth factor supporting stem cell self-renewal outside the nervous system and was previously shown to stimulate corneal epithelial proliferation both in vivo and in vitro. In this study, we evaluated the expression of NGF and its corresponding receptors in the human corneal and limbal tissues, as well as in primary limbal epithelial cultures by immunofluorescent staining and relatively quantitative real-time polymerase chain reaction. We found that NGF was uniquely expressed in the human limbal basal epithelium, together with its two corresponding receptors: the high-affinity receptor TrkA and the low-affinity receptor p75NTR. TrkA was shown to preferentially localize to limbal basal epithelial cells. NGF and TrkA were also found co-localized with stem cell-associated molecular markers (drug-resistance transporter ABCG2 and p63), but not with the differentiation marker cytokeratin 3 in the human limbal basal epithelial layer. In cultured limbal epithelial cells, NGF and TrkA were found to be preferentially expressed by a small population of limbal epithelial cells. The NGF and TrkA immuno-positive subpopulations were enriched for certain properties (including ABCG2 and p63 expression) of putative limbal epithelial stem cells (P <0.01, compared with the entire cell population). Levels of NGF and TrkA transcripts were found to be much more abundant in limbal than in corneal tissues, and in young cultured cells in the proliferative stage than in air-lifted stratified cultures containing differentiated cells. The co-expression of NGF with its two corresponding receptors in limbal basal epithelial cells, but not in the cornea, suggests that NGF may function as a critical autocrine or paracrine factor supporting stem cell self-renewal in the limbal stem cell niche. The spatial expression of NGF and TrkA by small clusters of basal cells interspersed between negative cell patches suggests that they are potential markers for human corneal epithelial progenitor cells.